The Large Time Convergence of Spectral Method for Generalized Kuramoto-Sivashinsky Equations (Journal of Computational Mathematics, 1997)
In this paper we use the spectral method to analyse the generalized Kuramoto-Sivashinsky equations. We prove the existence and uniqueness of global smooth solution of the equations. Finally, we obtain the error estimation between spectral approximate solution and exact solution on large time.